A educação rural concebida por organismos internacionais e suas repercussões no Brasil nas décadas de 1960 e 1970* - Celeste, Macioniro [UNESP] (ANPEd - Associação Nacional de Pós-Graduação e Pesquisa em Educação, 2019)
The paper deals with the divergent conceptions that international organisms dedicated to rural education in the 1960s and 1970s. It presents the ideal conceptions that United Nations Educational, Scientific and Cultural Organization (Unesco) and the Organization of American States (OAS) have dedicated to the theme. It highlights how Unesco's advisory economists have defined rural education hegemonically in this organization, as well as emphasizes the preponderance of the thinking of UNESCO’s economists as advisors in the implementation of rural education projects in the 1960s and 1970s. Differentiating from Unesco-related economists, the debate on rural education promoted by Economic Commission for Latin America and the Caribbean (Eclac) in the 1970s will deal with this issue in an innovative way. Finally, the conceptions that rural education found in Brazilian government agencies in the 1960s and 1970s will be presented. The research aimed to differentiate the possible influences of the international debate on rural education in the 1960s and 1970s and their interfaces with the discussion of this theme in Brazil in the same period.

El trabajo aborda las concepciones divergentes que los organismos internacionales dedicaron a la educación rural en las décadas de 1960 y 1970. Presenta las concepciones ideales que la Organización de las Naciones Unidas para la Educación, la Ciencia y la Cultura (Unesco) y la Organización de los Estados Americanos (OEA) dedicaron al tema. Destaca cómo los economistas asesores de la Unesco definieron la educación rural hegemónicamente en este organismo. Se enfatizará la preponderancia del pensamiento de los economistas vinculados a la Unesco como asesores en la implementación de proyectos de educación rural en las décadas de 1960 y 1970. Diferenciándose de los economistas vinculados a la Unesco, el debate sobre la educación rural promovido por la Comissión Económica para la America Latina y el Caribe (Cepal) en la década de 1970 tratará esta temática de manera innovadora. Finalizando el texto, se presentarán concepciones que la educación rural encontró en órganos gubernamentales brasileños en las décadas de 1960 y 1970. La investigación tuvo como objetivo diferenciar las posibles influencias del debate internacional sobre la educación rural en los años 1960 y 1970 y sus interfaces con la discusión de este tema en Brasil en el mismo período.

O trabalho aborda as concepções divergentes que os organismos internacionais dedicaram à educação rural nas décadas de 1960 e 70. Apresenta as concepções ideais que a Organização das Nações Unidas para a Educação, a Ciência e a Cultura (Unesco) e a Organização dos Estados Americanos (OEA) dispensaram ao tema. Verifica como os economistas assessores da Unesco definiram a educação rural hegemonicamente nesse organismo. É enfatizada a preponderância do pensamento dos economistas ligados à Unesco como assessores na implantação de projetos de educação rural nos anos de 1960 e 70. Diferenciando-se desses economistas, o debate sobre a educação rural promovido pela Comissão Econômica para a América Latina e o Caribe (Cepal) na década de 1970 tratou dessa temática de maneira inovadora. Finalizando o texto, são apresentadas concepções que a educação rural encontrou em órgãos governamentais brasileiros nas décadas de 1960 e 70. A pesquisa teve por objetivo diferenciar as possíveis influências do debate internacional sobre a educação rural nos anos 1960 e 70 e suas interfaces com a discussão desse tema no Brasil no mesmo período.
THE RURAL EDUCATION CONCEIVED BY INTERNATIONAL ORGANIZATIONS AND THEIR REPERCUSSIONS IN BRAZIL IN THE 1960S AND 1970S
LA EDUCACIÓN RURAL CONCEBIDA POR ORGANISMOS INTERNACIONALES Y SUS REPERCUSIONES EN BRASIL EN LAS DÉCADAS DE 1960 Y 1970
Keywords: rural education; history of education; international organizations of culture; educação rural; história da educação; organismos internacionais de cultura